Ketamine induced gut microbiota dysbiosis and barrier and hippocampal dysfunction in rats - Lei Xie; Zelin Zhuang; Baowen Guo; Yuehua Huang; Xiaoyan Shi; Zikai Huang; Ziquan Xu; Yanbin Chen; Yuyin Cao; Yanmin Zheng; Renhua Wu; Shuhua Ma (iScience)
Summary: The microbiota-gut-brain axis (MGBA) plays a pivotal role in drug addiction. However, the pathophysiological mechanism of MGBA in ketamine addiction remains elusive. The present study investigated the ketamine-induced gut microbiota disorders, intestinal barrier dysfunction, and the alterations in brain function, using a conditioned place preference (CPP) model of ketamine addiction in rats. Compared with the control group, ketamine induced decreased amplitude of low-frequency fluctuation (ALFF) values in the hippocampus, and pyknotic nuclei and concentrated cytoplasm in hippocampal neurons, as well as alterations in gut microbiota composition, shortened ileum villi, and thinner colonic mucosa. We also found that the abundance of gut microbiota exhibited correlations with CPP score, hippocampal ALFF value, length of ileum villi, and thickness of colonic mucosa. Our findings provide evidence for abnormal alterations in the MGBA of ketamine-addicted rats, which improves our understating of the mechanism of ketamine addiction and the potential for developing new therapeutic strategies.